Web and Internet Economics 13th International Conference, WINE 2017, Bangalore, India, December 17-20, 2017, Proceedings - Lu, Pinyan; R. Devanur, Nikhil (Springer Nature, 2017)
This book constitutes the thoroughly refereed proceedings of the 13th International Conference on Web and Internet Economics, WINE 2017, held in Bangalore, India, in December 2017. The 28 full and 6 short papers presented were carefully reviewed and selected from 89 submissions. The papers reflect the work of researchers in theoretical computer science, artificial intelligence, and microeconomics who have joined forces to tackle problems at the intersection of computation, game theory and economics.